Business Process Modeling A Logical Perspective - Panuška, Martin; Řepa, Václav, 1958-; Svatoš, Oleg; Vysoká škola ekonomická v Praze. Fakulta informatiky a statistiky (2009)
In the master's thesis we are concerned with the logical perspective on business process model-ing. The logical perspective on business process modeling has several advantages. First, being a formal logical system, first-order logic let us thoroughly understand the foundations of process modeling. Second, after we understand the logical foundations of business process modeling, we are free to build a BPM language based entirely on logic, or map an existing language onto logic, which may be useful for artificial reasoning. Third, if the business process model is mapped to logic (or another declarative language) it can be easily stored in a declarative knowledge base. Forth, logic based process models can be used in companies as a basis for knowledge manage-ment. And fifth, the science of logic offers a number of various semantic enhancements, which can be used in favor of better business process modeling expressiveness. The first objective of the thesis is to perform a thorough review of the literature of both our fields -- the business process modeling and temporal logic. The related second objective is to study the ability of logic to represent processes and the notion of time in general, and to offer techniques for logical process representation. Subsequently, the examples should be provided in order to present that the selected techniques are capable of performing what is sketched in the first paragraph. The third objective is to propose improvements of the current business process modeling approach and provide relevant examples. Eventually, means of extending the tech-niques presented can be proposed, too. The major contribution of the thesis is that it constitutes a reasonable basis for further research in the chosen field. For novices or even experienced in the subject it represents a good stepping stone.
Vedoucí práce: Václav Řepa
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Způsob přístupu: Internet
Diplomová práce (Ing.)—Vysoká škola ekonomická v Praze. Fakulta informatiky a statistiky, 2010
Rok obhajoby 2010
Keywords: informační systémy a technologie [obor dipl. práce]; diplomové práce; master's theses